Prospective comparison of thermometers used in very preterm infants. Issue 6 (7th May 2021) - Dunne, Emma A; O'Donnell, Colm Patrick Finbarr; McCarthy, Lisa K
Abstract : We measured temperature on admission to the neonatal unit in a cohort of 54 very preterm infants. We measured rectal temperature with a digital thermometer (Microlife MT-1931) as the gold standard (MT-R). We also measured axillary temperature with the MT (MT-A), with the Welch Allyn SureTemp Plus 692 in 'continuous' (WAC) mode and in the default 'predictive' (WAP) mode. While MT-A and WAC frequently differed from MT-R by ≥0.3°C, they were both reasonably sensitive and specific for hypothermia (MT-R <36.5°C). WAP overestimated MT-R by ≥0.5°C on 37/53 (70%) occasions and had poor sensitivity for hypothermia, identifying only 2 of 29 infants with MT-R <36.5°C as hypothermic.